2006
DOI: 10.1001/archpsyc.63.7.808
|View full text |Cite
|
Sign up to set email alerts
|

Gene Variants of Brain Dopamine Pathways and Smoking-Induced Dopamine Release in the Ventral Caudate/Nucleus Accumbens

Abstract: Smokers with genes associated with low resting dopamine tone have greater smoking-induced (phasic) dopamine release than those with alternate genotypes. These findings suggest that dopamine system genotype variabilities explain a significant proportion of the interindividual variability in smoking-induced dopamine release and indicate that smoking-induced dopamine release has a genetic predisposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
160
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(174 citation statements)
references
References 89 publications
(91 reference statements)
13
160
1
Order By: Relevance
“…For example, research on reward sensitivity showed that BOLD during reward anticipation and delivery, as well as during presentation of reward-related stimuli is larger for 9R carriers than 10R hetero-and homozygotes (Dreher et al, 2009;Forbes et al, 2009;Franklin et al, 2009). Direct support of enhanced striatal DA release in 9R carriers was obtained following smoking in a [ 11 C]raclopride PET study (Brody et al, 2006), in agreement with studies suggesting the 9R allele to be associated with enhanced dopaminergic output. Overall, Dreher et al (2009) conclude that '9R carriers, irrespective of the investigated domain, show hyper-responsivity of specific brain networks' (p 620), compatible with our finding of greater BOLD following MPH in 9R carriers than 10/10 homozygotes (however, see Wittmann et al, 2013).…”
Section: Pharmacogenetic Findingssupporting
confidence: 68%
“…For example, research on reward sensitivity showed that BOLD during reward anticipation and delivery, as well as during presentation of reward-related stimuli is larger for 9R carriers than 10R hetero-and homozygotes (Dreher et al, 2009;Forbes et al, 2009;Franklin et al, 2009). Direct support of enhanced striatal DA release in 9R carriers was obtained following smoking in a [ 11 C]raclopride PET study (Brody et al, 2006), in agreement with studies suggesting the 9R allele to be associated with enhanced dopaminergic output. Overall, Dreher et al (2009) conclude that '9R carriers, irrespective of the investigated domain, show hyper-responsivity of specific brain networks' (p 620), compatible with our finding of greater BOLD following MPH in 9R carriers than 10/10 homozygotes (however, see Wittmann et al, 2013).…”
Section: Pharmacogenetic Findingssupporting
confidence: 68%
“…After nicotine exposure, inhibitory effects of GABA are reduced and positive effects of glutamatergic and cholinergic projections are increased, resulting in increased dopamine release from VTA [19,27]. Smokers, DRD4 short allele carriers, who have low resting dopamine tone, had greater smoking-induced dopamine release than individuals with other DRD4 genotypes [4,32]. Brody et al [4] reported an association between decreased craving and increased dopamine concentration with smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Smokers, DRD4 short allele carriers, who have low resting dopamine tone, had greater smoking-induced dopamine release than individuals with other DRD4 genotypes [4,32]. Brody et al [4] reported an association between decreased craving and increased dopamine concentration with smoking. In DRD4 long allele carriers, the ability of dopamine to inhibit cAMP formation is decreased, and these individuals have a greater resting dopaminergic tone, and lower smoking-induced dopamine release than DRD4 short allele carriers [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the G allele of the CNR1 variant rs1049353 is associated with poorer antidepressant response and weaker striatal and thalamic response to happy faces (Domschke et al, 2008), whereas a genetic variant conferring reduced expression of NPY (the rs16147 C allele) is associated with greater amygdala reactivity to emotional faces in depressed patients, and with poorer treatment Imaging psychiatric pharmacogenetics M Falcone et al (Brody et al, 2006) Imaging psychiatric pharmacogenetics M Falcone et al response among a subgroup of patients with anxious depression (Domschke et al, 2010). Although limbic reactivity to emotional faces may provide a useful measure to identify likely treatment responders or for early medication screening, important limitations of these studies include the combined analysis of patients taking a range of medications (eg, tricyclics, SSRIs, neuroleptics) and the lack of randomization to medication vs placebo.…”
Section: Emotional Face Processing Assessed With Fmrimentioning
confidence: 99%